Learning-Supportive Environment Management in Schools Under The Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 - สุสุขเสียง สุมิตตา; ประวัติรุ่งเรือง ประเสริฐ; การีเวท สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) study the learning-supportive environment management in educational institutions; 2) compare the learning-supportive environment management in educational institutions classified by personal factors; and 3) explore guidelines for developing learning-supportive environments in educational institutions. The sample consisted of 309 school administrators and teachers under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 in the academic year 2025. The sample size was determined using the Krejcie and Morgan (1970) table. The research instruments included a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.80-1 and a reliability coefficient of 0.96, as well as a semi-structured interview form for development guidelines. The statistical methods used for data analysis were frequency, percentage, mean, standard deviation, t-test, and F-test. Qualitative data were analyzed using content analysis. The research findings revealed that 1) The overall and individual aspects of learning-supportive environment management in educational institutions under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 were at a high level. When considering each aspect, the academic aspect had the highest mean, followed by the physical aspect, while the administrative aspect had the lowest mean. 2) The comparison results showed that gender did not result in statistically significant differences. However, position, educational level, and work experience showed statistically significant differences at the .05 level, while school size showed statistically significant differences at the .01 level. 3) The development guidelines indicated that educational institutions should prioritize improving infrastructure and physical environments, along with enhancing academic work and instructional management, reducing teachers’ workload, promoting the use of technology, encouraging staff participation in operations, and improving communication systems for greater efficiency.